Pavement materials for heat island mitigation : design and management strategies - Li, Hui (Butterworth-Heinemann, 2015)
About 90 percent of this excessive heat is due to buildings and pavements that absorb and store solar heat (According to the Green Buildings Council). The only reference that focuses specifically on pavements, Pavement Materials for Heat Island Mitigation: Design and Management Strategies explores different advanced paving materials, their properties, and their associated advantages and disadvantages. Relevant properties of pavement materials (e.g. albedo, permeability, thermal conductivity, heat capacity and evaporation rate) are measured in many cases using newly developed methods. Include.